Characteristics of a large gap uniform discharge excited by DC voltage at atmospheric pressure - 李雪辰 鲍文婷 贾鹏英 赵欢欢 狄聪 陈俊英 (Chinese physics B, 2014)
A large-gap uniform discharge is ignited by a coaxial dielectric barrier discharge and burns between a needle anode and a plate cathode under a low sustaining voltage by feeding with flowing argon. The basic aspects of the large-gap uniform discharge are investigated by optical and spectroscopic methods. From the discharge images, it can be found that this discharge has similar regions with glow discharge at low pressure except a plasma plume region. Light emission signals from the discharge indicate that the plasma column is invariant with time, while there are some stochastic pulses in the plasma plume region. The optical emission spectra scanning from 300 nm to 800 nm are used to calculate the excited electron temperature and vibrational temperature of the large-gap uniform discharge. It has been found that the excited electron temperature almost keeps constant and the vibrational temperature increases with increasing discharge current. Both of them decreases with increasing gas flow rate.